Perfil eletroquímico e atividade alelopática de AgNPs por extrato aquoso de guaraná - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Pesticides are synthetic chemical products used to eliminate insects, larvae, fungi and ticks under the justification of controlling diseases caused by these vectors and regulating vegetation growth. Exposure to these compounds can cause a series of health effects, ranging from skin irritation, burning, dehydration, allergies to diseases such as leukemia, non-Hodgkin lymphomas, pancreatic cancer and lung cancer, depending on the product used, the exposure time and amount of product absorbed by the body. In this context, the degradation of pesticides has aroused the interest of the scientific community, so advanced electrochemical oxidative processes (PEOAs) are very attractive, because they are capable of degrading a series of pollutants. In this sense, silver nanoparticles (AgNPs) mediated by plant extracts emerge as an alternative to be used as catalysts, since they are produced from plant extracts and these have biomolecules that are capable of reducing and stabilizing AgNPs, generating products or by-products of low toxicity to the environment. In this work, the synthesized AgNPs were applied in the electrochemical degradation process of the pesticide deltamethrin, which is used to control TRIPES in guarana trees. The nanoparticles were produced at pH 9.0 using 1g of guarana powder in 100 mL of water, at temperatures of 30 ºC and 60 ºC in the in situ and ex situ process and the synthesis process was monitored via UV-vis electronic spectroscopy. from the appearance of the band with a maximum at 410 nm. Confirmation of the behavior of the RPS band obtained during the synthesis suggests spheroidal-type AgNPs. The XRD data correspond to the cubic phase of silver, which is more intense for the in situ AgNPs/CA sample. The SEM analysis shows the morphology of rounded clusters. The information obtained by EDX techniques complements this observation, suggesting AgNPs/CA only in the ex situ process. The results obtained from the electrochemical characterization show good activity of the AgNPs electrocatalyst against the electrooxidation of deltamethrin, which was monitored via cyclic voltammetry in 0.5 mol L-1 of KCl. The cyclic voltammogram of AgNPs obtained ex situ shows a signal at 1.0 V referring to the oxidation of Ag0→Ag+ and 0.9 V referring to the reduction of Ag+→Ag0. In the presence of deltamethrin, oxidation was observed at 1.0 V and reduction at 0.7 V. Detection data from the ex situ and in situ process suggest linearity R2=0.9977 in situ, and for ex situ R2= 0.9910. It was observed that AgNPs mediated by Paullinia cupana guarana extract had a high potential for allelopathic effect on gherkin and coriander seeds, delaying their growth.
Keywords: Pragas agrícolas - Controle biológico; Guaraná - Mudas - Controle biológico; CIENCIAS EXATAS E DA TERRA; Paullinia cupana; Biorredutor; Nanotecnologia; Eletrooxidação